PENGARUH KEPEMIMPINAN TRANSAKSIONAL DAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA DI PDAM TIRTAWENING KOTA BANDUNG - , ANTONIUS YUCA PRABOWO, Dr. Tarsisius Hani Handoko, M.B.A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to determine the effect of transactional leadership and transformational leadership on job satisfaction in Perusahaan Daerah Air Minum (regional water company) Tirtawening Bandung. This study also discusses the effect of augmentation that occurred between transactional leadership and transformational leadership in relation to job satisfaction. Research conducted in this study is testing the hypothesis with hierarchical regression method. A research instrument to collect the data is closed-ended questionnaire with purposive sampling technique. The number of respondents in this study is 67 employees who already working at the company and under a manager / supervisor for at least 1 year. The results of this study indicate that transactional leadership and transformational leadership has positive and significant effect on employee job satisfaction in PDAM Tirtawening Bandung. Transformational leadership also provides additional variable variant explanation toward employee job satisfaction variables than can be explained by transactional leadership.